Quotient space based problem solving : a theoretical foundation of granular computing - Zhang, Ling.; Zhang, Bo. (Waltham, MA : Morgan Kaufmann, 2014)
Provides an in-depth treatment of hierarchical problem solving, computational complexity, and the principles and applications of multi-granular computing, including inference, information fusing, planning, and heuristic search.
Chapter 1. Problem representations -- chapter 2. Hierarchy and multi-granular computing -- chapter 3. Information synthesis in multi-granular computing -- chapter 4. Reasoning in multi-granular worlds -- chapter 5. Automatic spatial planning -- chapter 6. Statistical heuristic search -- chapter 7. The expansion of quotient space theory.
Online resource; title from title page (viewed Feb. 21, 2014).
Includes bibliographical references (pages 375-379) and index.
Keywords: Granular computing; Mathematics; COMPUTERS -- General; Mathematics; Granular computing; Electronic books